The application of a dual-lead locking screw could enhance the reduction and fixation stability of the proximal humerus fractures: a biomechanical evaluation - Lee, Eunju; Jeong, Hyeon Jang; Lee, Yeon Soo; Oh, Joo Han (Frontiers in Surgery, 2024)
Introduction:Bicortical screw fixation, which penetrates and fixes the near and far cortex of bone, has been conventionally used to achieve compressive fixation for fracture using screws. When doing open internal fixation using the locking plate, minimal contact between the bone and the locking plate can lead to an insufficient reduction. Theoretically, a dual-lead locking screw with different leads for the screw head and body could enhance the reduction and fixation stability of fragments in proximal humeral fractures without bicortical fixation, and achieve additional compression at the bone-plate-screw interface. This study assessed the insertion mechanics of the lead ratio of the dual-lead locking screw and its effect on the fixation stability of the proximal humerus fracture.Methods:A Multi-Fix ® locking plating system composed of ∅3.5 mm locking screws and a locking plate was used to make a locked plating for Sawbone bone blocks and fourth-generation composite humeri. Two different types of Sawbone bone blocks were used to simulate the osteoporotic (10 PCF) and normal cancellous (20 PCF) bones. The lead of the screw head thread (𝐿𝐿 ℎ𝑒𝑒𝑒𝑒𝑒𝑒 ) was 0.8 mm, and that of the screw body (𝐿𝐿 𝑏𝑏𝑏𝑏𝑒𝑒𝑏𝑏 ) was 0.8, 1.25, 1.6, 2.0, and 2.4 mm, whose lead ratios (𝑅𝑅 𝑙𝑙𝑒𝑒𝑒𝑒𝑒𝑒 =𝐿𝐿 𝑏𝑏𝑏𝑏𝑒𝑒𝑏𝑏 /𝐿𝐿 ℎ𝑒𝑒𝑒𝑒𝑒𝑒 ) were 1.0, 1.56, 2.0, 2.5, and 3.0, respectively.The dual-lead locking screw elevated the compression between the locking plate and the bone. The elevation in the compression due to the dual-lead thread became weaker for the cancellous bone when the lead of the screw body was more than twice that of the screw head. The plate/humerus compression with strong bone quality withstood higher dual-lead-driven compression.Discussion:A dual-lead locking screw of 𝐿𝐿 𝑏𝑏𝑏𝑏𝑒𝑒𝑏𝑏 =1.25 mm (𝑅𝑅 𝑙𝑙𝑒𝑒𝑒𝑒𝑒𝑒 =1.56) is recommended for maximum rotational stability for the locked humerus plating. The screws with over 𝐿𝐿 𝑏𝑏𝑏𝑏𝑒𝑒𝑏𝑏 =1.6 mm (𝑅𝑅 𝑙𝑙𝑒𝑒𝑒𝑒𝑒𝑒 =2) have no advantage regarding the failure torque and maximum torsional deformation. Any locking dual-lead screw with a body thread lead of <1.6 mm (𝑅𝑅 𝑙𝑙𝑒𝑒𝑒𝑒𝑒𝑒 =2) can be used without the risk of bone crush when surgeons require additional compression to the locked cancellous bone plating.